2015
DOI: 10.2147/ijwh.s77202
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of dienogest in endometriosis: pooled analysis from the European clinical study program

Abstract: BackgroundIn four randomized, controlled, European trials, dienogest 2 mg once daily demonstrated significant efficacy for lesion reduction and reduction in pain intensity in endometriosis. We describe a pooled analysis of the safety and tolerability data from these trials to confirm and further characterize the safety profile of dienogest in the treatment of endometriosis.MethodsAll 332 women treated with dienogest 2 mg who participated in the four clinical trials were included in the pooled analyses for safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 34 publications
(63 reference statements)
2
48
2
2
Order By: Relevance
“…Previous studies reported a slight hypoestrogenic effect of dienogest after 52 or 65 weeks of treatment . Our result was consistent with that of the previous reports, and we showed that dienogest is tolerable for long‐term use.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous studies reported a slight hypoestrogenic effect of dienogest after 52 or 65 weeks of treatment . Our result was consistent with that of the previous reports, and we showed that dienogest is tolerable for long‐term use.…”
Section: Discussionsupporting
confidence: 93%
“…Our result was consistent with that of the previous reports, and we showed that dienogest is tolerable for long‐term use. Estradiol levels in dienogest treatment, unlike those in GnRH agonist treatment, were maintained with low physiologic range and without inducing hypoestrogenic effects, thereby indicating that dienogest is tolerable and preferable for long‐term use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the progestins, the 19-nortestosterone derivatives are less androgenic and offer better side effect profiles (Angioni et al 2014). In a RCT, dienogest significantly decreases endometriosis-related pain similar to gonadotropin releasing hormone agonists (GnRHa), both as initial and post-operative therapy, without the negative side effect profile of GnRHa (Angioni et al 2014, Andres Mde et al 2015, Granese et al 2015, Strowitzki et al 2015). Levonorgestrel, delivered through an intrauterine system after conservative surgery, significantly decreases dysmenorrhea, dyspareunia, and non-cyclic pelvic pain compared to expectant management in a RCT of 55 patients (Tanmahasamut et al 2012, Imai et al 2014).…”
Section: Treatmentsmentioning
confidence: 99%
“…In a pooled analysis of four clinical trials, dienogest 2 mg was well tolerated, with a favorable safety profile extending for up to 65 weeks. The most commonly reported adverse events were headache, breast discomfort, depressed mood, and acne, each occurring in <10% of patients, which were generally mild to moderate in intensity and associated with low discontinuation rates 41 . Administration of dienogest for up to 5 years has also demonstrated a favorable safety and tolerability profile [29][30][31][32][33][34] .…”
Section: Search Criteria: Visanne and Oral Contraceptives For The Trementioning
confidence: 99%